Avoided emissions of a fuel-efficient biomass cookstove dwarf embodied emissions. (June 2016) - Wilson, D.L.; Talancon, D.R.; Winslow, R.L.; Linares, X.; Gadgil, A.J.
Abstract: Three billion people cook their food on biomass-fueled fires. This practice contributes to the anthropogenic radiative forcing. Fuel-efficient biomass cookstoves have the potential to reduce CO2 -equivalent emissions from cooking, however, cookstoves made from modern materials and distributed through energy-intensive supply chains have higher embodied CO2 -equivalent than traditional cookstoves. No studies exist examining whether lifetime emissions savings from fuel-efficient biomass cookstoves offset embodied emissions, and if so, by what margin. This paper is a complete life cycle inventory of "The Berkeley–Darfur Stove, " disseminated in Sudan by the non-profit Potential Energy. We estimate the embodied CO2 -equivalent in the cookstove associated with materials, manufacturing, transportation, and end-of-life is 17 kg of CO2 -equivalent. Assuming a mix of 55% non-renewable biomass and 45% renewable biomass, five years of service, and a conservative 35% reduction in fuel use relative to a three-stone fire, the cookstove will offset 7.5 tonnes of CO2 -equivalent. A one-to-one replacement of a three-stone fire with the cookstove will save roughly 440 times more CO2 -equivalent than it "costs" to create and distribute. Over its five-year life, we estimate the total use-phase emissions of the cookstove to be 13.5 tonnes CO2 -equivalent, and the use-phase accounts for 99.9% of cookstove life cycle emissions. The dominance of use-phase emissions illuminate two important insights: (1) without a rigorous program to monitor use-phase emissions, an accurate estimate of life cycle emissions from biomass cookstoves is not possible, and (2) improving a cookstove's avoided emissions relies almost exclusively on reducing use-phase emissions even if use-phase reductions come at the cost of substantially increased non-use-phase emissions.